Dispersion Characteristics of Accidental LPG Release in Marine Engine Room - Phan Anh Duong; Hokeun Kang (Modelling and Simulation in Engineering)
Rising environmental awareness and the implementation of stricter maritime emission regulations have accelerated the search for sustainable fuel alternatives in the shipping industry. Liquefied petroleum gas (LPG) has emerged as a viable, ecofriendly option, offering a practical route toward achieving zero-emission vessels. This study investigates the safety implications of accidental LPG releases during operations within the engine room (14 m×8.26 m×3.8 m) of a 299 GT general cargo vessel equipped with a 789 HP engine. Specifically, it examines scenarios involving LPG leaks (70% propane and 30% n-butane) from pipeline punctures with diameters ranging from 50 to 150 mm, where the gas release lasts 30 s before the activation of the emergency shutdown system halts the supply. The rapid release of LPG due to equipment punctures can generate dispersive gas clouds, posing risks to personnel and adjacent areas. To evaluate these risks, a computational fluid dynamics (CFD) model was developed to simulate the dispersion behavior of LPG under various leak parameters (size, rate, and direction) and ventilation conditions in congested environments. The study identifies and analyzes key factors influencing gas dispersion and provides recommendations to mitigate the associated risks. The simulations employed the realizable k−ε turbulence model to effectively capture the dynamics of gas dispersion. Despite LPG’s high dispersion potential within confined spaces, its narrow flammability range (1.81%–8.86%) reduces the likelihood of ignition under typical dispersion scenarios. Results indicate that leaks within the 50–150 mm diameter range generally pose low ignition risks due to limited gas concentrations and ventilation-driven dispersion patterns. However, timely detection and response remain critical for minimizing hazards. This research provides valuable insights for regulatory authorities and industry stakeholders, offering practical guidance on fire safety compliance, emergency response protocols, and preventive measures to enhance the safety of maritime operations and surrounding facilities.